2013
DOI: 10.3727/096368912x663532
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Autologous Olfactory Ensheathing Cells in Complete Human Spinal Cord Injury

Abstract: Numerous studies in animals have shown the unique property of olfactory ensheathing cells to stimulate regeneration of lesioned axons in the spinal cord. In a Phase I clinical trial, we assessed the safety and feasibility of transplantation of autologous mucosal olfactory ensheathing cells and olfactory nerve fibroblasts in patients with complete spinal cord injury. Six patients with chronic thoracic paraplegia (American Spinal Injury Association class A-ASIA A) were enrolled for the study. Three patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
183
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(191 citation statements)
references
References 53 publications
(71 reference statements)
5
183
0
1
Order By: Relevance
“…OECs are able to promote axonal outgrowth by secreting growth factors such as NGF. 26,27 OM-MSCs can proliferate rapidly in vitro. Furthermore, OM-MSCs have the multiple potential to differentiate into cartilage, bone, smooth muscle and nerve cells.…”
Section: Introductionmentioning
confidence: 99%
“…OECs are able to promote axonal outgrowth by secreting growth factors such as NGF. 26,27 OM-MSCs can proliferate rapidly in vitro. Furthermore, OM-MSCs have the multiple potential to differentiate into cartilage, bone, smooth muscle and nerve cells.…”
Section: Introductionmentioning
confidence: 99%
“…Lima et al reported that the transplantation of minced olfactory mucosa in patients with chronic SCI was not significantly efficient (44). By contrast, recent clinical studies suggested that there was a neurological improvement in SCI patients after OEC transplantation (44,45).…”
Section: Olfactory Ensheathing Cellsmentioning
confidence: 99%
“…Due to their ability to guide the connections between the peripheral nervous system and the central nervous system, as well as their ability to differentiate into nonolfactory cell types, these cells are excellent candidates for cell transplantation [35] . These multipotent cells have been extensively studied in cases of spinal cord injury, and authors have reported that transplants were safe and patients experienced motor and sensory improvement, as well as recovered bladder function and activity of several muscles below the injury level [36,37] . In an amyotrophic lateral sclerosis (ALS) clinical trial conducted with OECs in China, researchers reported that patients experienced no benefits, two patients had severe side effects and one even died following transplantation [38] .…”
Section: Olfactory Ensheathing Cellsmentioning
confidence: 99%